Response of Water Balance Components to Changes in Soil Use and Vegetation Cover Over Three Decades in the Eastern Amazon - Silva-Júnior, Renato Oliveira da; Souza-Filho, Pedro Walfir Martins e; Salomão, Gabriel Negreiros; Tavares, Alexandra Lima; Santos, Jorge Filipe dos; Santos, Diogo Corrêa; Dias, Luanna Costa; Silva, Marcio Sousa da; Melo, Adayana Maria Queiroz de; Costa, Carlos Eduardo Aguiar de Souza; Rocha, Edson José Paulino da (Frontiers in Water, 2021)
Impacts on global water resources may be intensifying due to the growing and differentiated forms of land use and occupation, which influence the water cycle and thus the maintenance of life. In the Amazon, the effect may be even worse, as it is one of the world's most vulnerable regions to these changes. This work aimed to analyze the response of the components of the water balance to changes in land use and cover in the Eastern Amazon over three decades (1980–2013). First, soil texture maps were prepared. These combined with the classes of use in each decade let us estimate the values of storage and variation in storage (ΔS) of water in the soil. The behavior of the components of the water balance [precipitation, potential evapotranspiration, actual evapotranspiration (E), and ΔS] were analyzed according to the Budyko model on the annual scale as a function of the aridity and evaporative indices. For the seasonal scale, a new parameter (y0) was introduced to explicitly represent the additional water available for E, in addition to instantaneous precipitation. The seasonality of the rains and the seasonal dynamics of storage were directly incorporated into the model developed, which allowed us to understand what the dominant control factors of water balance are. In the decade from 2000 to 2009, the remaining forest cover is only 48.91%, while the cover formed by pasture is 50.47%, meaning the water storage capacity in the soil decreased 8.1%. In the 1990s, to 1999, precipitation shows a reduction, probably as a reflection of the very strong events of La Niña and El Niño (1988–1989 and 1997–1998). Observing the sum of the surface area of water bodies in the region and the relationship of forest vs. pasture, it is possible to infer that the elevation in evapotranspiration is more related to the increase in evaporation due to the increase in the pasture area than to the reduction transpiration due to forest loss, reinforcing the hypothesis that evapotranspiration increases with pasture area.